A novel management for postprostatectomy urinary incontinence: platelet-rich plasma urethral sphincter injection - Lee, Ping-Jui (Sci Rep, 2021)
Platelet-rich plasma (PRP) is the most innovative blood-derived product used in regenerative medicine. We aimed to investigate the therapeutic efficacy of PRP urethral sphincter injection for the management of postprostatectomy incontinence (PPI). In total, 28 PPI patients with a mean age of 71.8 ± 8.9 years were prospectively enrolled. They received four PRP urethral sphincter injections each month. The clinical outcomes were assessed 3 months after the fourth injection as posttreatment Global Response Assessment (GRA) score, the newly designed visual analogue scale of stress urinary incontinence (VAS of SUI), and in urodynamic parameters. After injections, the posttreatment median GRA with quartiles was 2.0 (1.0, 2.0). Overall, six (21.4%) patients achieved complete continence and pad-free status, 20 (71.4%) achieved successful outcome (GRA score ≥ 2), and 26 (92.9%) showed clinical improvement (GRA score ≥ 1). The VAS of SUI significantly improved from 6.5 (5.0, 8.0) to 3.5 (2.0–5.8) (p < 0.001) as well as abdominal leak point pressure, from 57.5 (50.0, 115.0) to 126.0 (68.3, 150.0), (p = 0.004). After repeated PRP urethral sphincter injections, the SUI severity reduced significantly with high success rates. There was no major adverse event, except three patients with mild hematuria and micturition pain. In conclusion, PRP urethral sphincter injection is safe and effective as a novel management of PPI.